IMPLEMENTASI PEMBELAJARAN MEMBACA TEKS PETUNJUK DENGAN MODEL PROJECT BASED LEARNING BERBANTUAN SALINDIA INTERAKTIF & DENAH - Nurul Hidayah; Sri Sumartiningsih; Philip X. Fuchs; Tri Joko Raharjo; Wadiyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Based on observations on 4th grade student of SD Labschool UNNES, researchers found several problems, there are lack of understanding of students in learning Instruction text, lack of active participation of students in learning, and the learning methods used by teachers were less communicative. This research aims to describe the application of reading Instruction text with the the PjBL model assisted by Interactive Slide and Direction for grade 4 of elementary school students. The focus of this research is: (1) Reading Instruction text (2) Steps to the PjBL learning model (3) Interactive slide and Direction. The approach in this research is qualitative research, the research object is Indonesians subject. The subjects of this research are: (1) activities reading Instruction text using the PjBL model assisted by Interactive slide and Direction. (2) the student of grade 4. (3) The teacher of grade 4. The method used in this research is descriptive method. Data collection techniques are observation techniques, work on LKPD, and project creation by students. Data processing was carried out using qualitative descriptive analysis. The research results showed that students' understanding of learning in reading Instruction text using the PjBL learning model assisted by Interactive slide increased and Direction. Based on these results, the use of the PjBL learning model assisted by Interactive Slide and Direction has an influence on the understanding of learning concepts for 4th grade student of Elementary School.